Hubungan Antara Growth Mindset dan Hasil Belajar Peserta Didik Pada Pembelajaran IPS di Sekolah Dasar: Penelitian Kuantitatif - Alfiyyah Alifah Ahmad; Muh Ayyub Alfajri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to determine the relationship between Growth Mindset and Learning Outcomes of Elementary School Students. This study is a Quantitative Research with a pre-experimental one group pretest-posttest design conducted on elementary school students. The research subjects were 15 students. Data were collected through observation, questionnaires, tests and documentation, then analyzed descriptively quantitatively. The results showed that there was an increase in learning outcomes with an average pretest score of 66.67 to 87.20 in the posttest. Based on the Shapiro-Wilk normality test, the data were declared normally distributed so that the test was continued using a paired sample t-test with a t-count result of 6.118 with a significance of 0.00 <0.05 which means there was a significant increase after treatment. To see the relationship between growth mindset and learning outcomes, a correlation test was used, where the results of the correlation test obtained a value of r = 0.451 which means the correlation value is in the interval 0.40-0.599. This indicates that growth mindset has a moderate relationship to student learning outcomes